Psychological Care Center for Depression and Anxiety Sufferers in Jakarta with Biophilic Approach - Najwa Chika Salsabila Najwa Chika Salsabila (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2023)
Mental health problems continue to increase in Indonesia, with depression and anxiety being the number with the most sufferers. However, mental health service facilities in DKI Jakarta are still minimal, even though this province has a high prevalence rate of mental disorders, reaching 10.1%. In addition, the existing mental health services often ignore environmental factors, so the therapy process is not optimal. In fact, according to Kaplan (2010), 40% of patient healing factors are environmental factors. Biophilic architecture is a design approach that connects humans with nature that is able to improve the well-being of human life both physically and mentally. This design is intended to create a mental health service center that can assist patients in an optimal healing process with a biophilic approach. With a biophilic pattern, namely, visual connection with nature, non-visual connection with nature, thermal and airflow variability, presence of water, material connection with nature, and prospects which are translated into design criteria, then applied to the design elements of the Psychological Care Center which includes landscape layout, building forms, building systems, and also interiors.